Implementasi Peraturan Walikota Nomor 26 Tahun 2018 Tentang Pedoman Pengarusutamaan Gender (PUG) Kota Padang Panjang Ditinjau Dari Perspektif Maslahah - Warman, Septia (HK-Publishing, 2023)
AbstractGender mainstreaming has an important role in national development which later gave birth to Mayor Regulation Number 26 of 2018 concerning references for the PUG program in the city of Padang Panjang. For the PUG program in Padang Panjang City, the Regional Government as the institution that regulates and is obliged to implement PUG in Padang Panjang City to create gender equality between men and women, one of which is women's issues, unequal rights and obligations of men and women in many aspects. The aim of this thesis is to find out: (1) Implementation of Mayor Regulation number 26 of 2018 concerning Gender Mainstreaming in the City of Padang Panjang (2) Perwako Padang Panjang Number 26 of 2018 concerning Gender Mainstreaming in the City of Padang Panjang viewed from a Maslahah perspective. This article is field research using descriptive methods, which provide a detailed description of the problem according to reality. The informants in this research are the Mayor of Padang Panjang, the Head of the Regional Apparatus Organization (OPD) which makes gender mainstreaming policies as well as experts and specialists in the field of gender mainstreaming. To obtain data the author used observation, interview and documentation techniques. In general, the policy formulation process that has been carried out by the Padang Panjang City Government is in accordance with the Gender-based policy formulation used by the OPD and the stages of policy formulation that have been implemented have met the PUG criteria. Apart from that, the issuance of Mayor Regulation Number 26 of 2018 has become evidence of gender mainstreaming efforts that have been implemented by the Padang Panjang City Government when viewed from a maslahah perspective.Keywords: Gender Mainstreaming, Maslahah, RegulationsÂ AbstrakPengarusutamaan gender mempunyai peranan penting dalam pembangunan Nasional yang kemudian melahirkan Peraturan Walikota Nomor 26 Tahun 2018 tentang acuan program PUG di kota Padang Panjang. Untuk program PUG di Kota Padang Panjang, Pemda sebagai institusi yang mengatur dan berkewajiban untuk melaksanakan PUG di Kota Padang Panjang untuk meciptakan kesamaan gender antara laki-laki dan wanita yang salah satunya merupakan masalah wanita, ketidak setaraan hak dan kewajiban laki-laki dan wanita dalan banyak aspek. Tujuan tesis ini adalah untuk mengetahui: (1) Pelaksanaan Peraturan walikota nomor 26 Tahun 2018 tentang Pengarusutamaan Gender kota Padang Panjang (2) Perwako Padang Panjang Nomor 26 Tahun 2018 tentang Pengarusutamaan Gender Kota Padang Panjang ditinjau dari perspektif Maslahah. Tulisan ini adalah penelitian lapangan (field research) dengan menggunakan metode deskriptif, yang memberikan gambaran secara terperinci terhadap permasalahan sesuai kenyataan. Informan dalam penelitian ini adalah Walikota Padang Panjang, Kepala Organisasi Perangkat Daerah (OPD)yang membuat kebijakan pengarusutamaan gender serta para ahli dan pakar di bidang pengarusutamaan gender. Untuk memperoleh data penulis menggunakan teknik observasi, wawancara dan dokumentasi. Secara garis besar proses formulasi kebijakan yang telah dilakukan oleh Pemerintah Kota Padang Panjang sudah sesuai dengan formulasi kebijakan yang berbasis Gender yang digunakan oleh OPD dan tahapan perumusan kebijakan yang telah dilaksanakan sudah memenuhi kriteria PUG. Selain itu, dengan lahirnya Peraturan Walikota Nomor 26 tahun 2018 telah menjadi bukti dari upaya pengarusutamaan gender yang sudah dilaksanakan oleh Pemerintah Kota Padang Panjang apabila ditinjau dari perspektif maslahah.Â Kata Kunci:Â Pengarusutamaan Gender, Maslahah, Peraturan